Phytochemical-Stabilized Platinum-Decorated Silver Nanocubes INHIBIT Adenocarcinoma Cells and Enhance Antioxidant Effects by Promoting Apoptosis via Cell Cycle Arrest - Adewale Odunayo Oladipo; Jeremiah Oshiomame Unuofin; Sogolo Lucky Lebelo; Titus Alfred Makudali Msagati (MDPI AG, 2022)
(1) Background: The increasing use of silver and platinum bimetallic nanoparticles in the diagnosis and treatment of cancer presents significant advances in biomedical applications due to their extraordinary physicochemical properties. This study investigated the role of aqueous phytochemical extract in stabilizing platinum nanodots-decorated silver nanocubes (w-Pt@AgNPs) for enhancing antioxidant activities and their mechanism. (2) Methods: UV-Vis, Fourier transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM) were used to characterize the formed w-Pt@AgNPs. LC-QToF-MS/MS was used to analyze the bioactive compounds, while DPPH, ABTS, and FRAP were used to detect the scavenging potential. Flow cytometric assays were performed to investigate the cytotoxicity and the mechanism of cell death. (3) Results: Morphological studies indicated that w-Pt@AgNPs were cube in shape, decorated by platinum nanodots on the surfaces. Compared to ethanolic extract-synthesized e-Pt@AgNPs, w-Pt@AgNPs exhibited the strongest antioxidant and cytotoxic activity, as data from Annexin V and Dead cell labeling indicated higher induction of apoptosis. Despite the high proportion of early apoptotic cells, the w-Pt@AgNPs triggered a decrease in G1/G0 cell cycle phase distribution, thereby initiating a G2/M arrest. (4) Conclusions: By enhancing the antioxidant properties and promoting apoptosis, w-Pt@AgNPs exhibited remarkable potential for improved cancer therapy outcomes.